Finite Time Disturbance Observer Based Geometric Control of Quadrotors. (2020) - Sharma, Manmohan; Kar, Indrani
Abstract: This paper proposes a finite time disturbance observer based geometric controller for quadrotors utilizing the rotation matrices for attitude dynamics. Mathematical proof has been given to show that the closed loop errors are bounded before the disturbance has been estimated by the finite time disturbance observer. After the disturbance has been estimated by the finite time disturbance observer in certain finite time, the closed loop error dynamics is shown to be exponentially stable. Numerical simulation results have been given to demonstrate the proposed result. The proposed method has been developed on the nonlinear manifold SE(3) where the attitude dynamics evolve on SO(3) and the translational dynamics evolve on R 3 .